Keharmonisan Rumah Tangga Perspektif Hukum Islam - Subairi Subairi (Mabahits : Jurnal Hukum Keluarga Islam, 2021)
Islam is very concerned about the safety of its adherents, so that all forms of legislation that are applied must contain benefits. Not only in terms of worshiping God but also regarding the relationship between fellow human beings. If it is narrowed again in terms of the household, Islam also regulates it. Not only telling followers to marry as the beginning of a household, but how to build an ideal household which is then discussed with the Sakinah family, namely, harmonious and pleasant. However, not many people really understand what must be done in building a harmonious family, as reflected in many families ending in divorce. From this problem, the author wishes to examine what things must be done in building family harmony, this research uses a qualitative approach that is library research, and the data collection technique uses a documentary study of books, scientific works and literature. scientific journal. After conducting research which continued to analyze any data obtained, the researchers concluded that to build a harmonious family there are at least three things that must be considered. First, build a good understanding between husband and wife so that it can produce good results. Second, be tolerant between the two of them, by continuing to instill in their minds that humans were created in a weak state. Third, be reasonable with your partner, because anything if done excessively will have a bad impact, such as being disappointed in the future, even in the context of a family, it will result in divorce.